Egg-laying hormone, serotonin, and cyclic nucleotide modulation of ionic currents in the identified motoneuron B16 of Aplysia - Kirk, MD (J Neurosci, 1988)
We have used the 2-electrode voltage-clamp technique to analyze the effects of the neuropeptide, egg-laying hormone (ELH), and the biogenic amine 5-HT on ionic currents in the buccal motoneuron B16 of Aplysia. When B16 is voltage-clamped near resting membrane potential, bath- applied ELH induces a prolonged inward shift in holding current. The ELH-induced inward current is not due to a decrease in the transient, the delayed, or the calcium-activated potassium currents. Current- voltage measurements, along with ion substitution and channel-blocking experiments, indicate that ELH primarily induces or increases a voltage- dependent slow inward current carried by sodium. Serotonin also causes a prolonged inward shift in holding current in B16. Like ELH, 5-HT induces or enhances the voltage-dependent inward current carried by sodium. In addition, 5-HT increases an inwardly rectifying potassium current, and, in some preparations, decreases an outward current that is activated when the cell is depolarized to -40 mV and above. None of the currents modulated by ELH or by 5-HT are affected by 200 microM ouabain or by reducing extracellular chloride concentration. Extracellular application of isobutylmethylxanthine (IBMX), forskolin, 8-bromo-cAMP and 8-bromo-cGMP, and intracellular injection of cAMP elicits the slow inward current carried by sodium. The inward current response to ELH is blocked by prior application of 8-bromo-cAMP, while, under these conditions, 5-HT continues to elicit the increase in inward- rectifier potassium current, but decreases the slow inward sodium current. Serotonin also reduces the slow inward sodium current when applied after ELH. These results suggest that the modulation of B16 by ELH may be mediated entirely by either cAMP or cGMP, while at least a portion of the response to 5-HT may involve an unidentified second messenger in addition to cyclic nucleotides.